2018
DOI: 10.2174/1874210601812010303
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Comparison of Total Antioxidant Capacity of Saliva Between Patients with Recurrent Aphthous Stomatitis and Healthy Subjects

Abstract: Background & Objectives: Recurrent Aphthous Stomatitis (RAS) is one of the most common chronic ulcerative lesions of the oral mucosa and its development may be associated with oxidative stress. The aim of this study was to evaluate salivary Total Antioxidant Capacity (TAC) in patients with minor RAS.Materials & Methods:In this case-control study, 27 patients with minor RAS and 28 age- and sex-matched controls without RAS were enrolled. TAC was measured in unstimulated saliva for patients (during active lesion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…On the other hand, the effects of oxidative stress in the oral cavity have proven to contribute to chronic inflammatory periodontal diseases, RAS, oral lichen planus, etc. [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the effects of oxidative stress in the oral cavity have proven to contribute to chronic inflammatory periodontal diseases, RAS, oral lichen planus, etc. [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…The oxidant-antioxidant status changes in the saliva depend on many factors, making the interpretation of occurred changes difficult (REZAEI & SOULTANI [13]).…”
Section: Discussionmentioning
confidence: 99%
“…1. like a defense mechanism against the tissue inflammation changes (a compensatory response against oxidative stress caused by periodontal disease) 2. having oral pain change the diet with taking more liquid food and juices that are generally rich in nutrients, vitamins and antioxidant compounds, thereby improving antioxidants status of whole body and saliva (REZAEI & SOULTANI [13]). Some studies have demonstrated the effect of nutrition on antioxidant levels of saliva to support this possibility (green tea intake increase the TAC of whole saliva in adults with significant periodontal problems (BAKHTIARI & al.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that the imbalance between oxidation and antioxidation is one of the causes of tissue damage in patients with RAU [6] . Malondialdehyde (MDA), one of the stable end products of lipid peroxidation, represents the aggravation of lipid peroxidation.…”
Section: Recurrent Aphthous Ulcer and Oxidative Stressmentioning
confidence: 99%